Mapping environmental contamination of carbon footprints and health impact from the breastmilk substitutes consumption in Southeast Asia: A scoping review - Kusmayra Ambarwati; Andini Pramono (Journal of Evidence-based Nursing and Public Health, 2026)
Background: In Southeast Asia, breastmilk substitutes (BMS) have quickly turned into a widely accepted social practice. But the health and environmental effects are not thoroughly examined. BMS producers and manufacturers, through their industrial processes, packaging waste, and transportation, are the major contributors to ecological degradation, while formula feeding brings health risks for infants. Methods: This scoping review was performed in accordance with the PRISMA-ScR guidelines and brought together results from 23 articles published in reputable journals between 2015 and 2025. The databases explored were PubMed, Scopus, Cochrane Library, Google Scholar, and Crossref. Data was gathered, and the latter was done through the Joanna Briggs Institute tools, and then it was analyzed thematically. Findings: There is a clear link between BMS production and consumption, and major environmental impacts resulting from these 3-MCPD, glycidyl esters are examples of chemical contaminants; microplastics and large amounts of GHG emissions are also included (3–6 kg CO₂-eq per kg product). Water and energy use are augmented due to formula preparation, and the disposal of materials has worsened plastic pollution in urban rivers. Health investigations pointed out that babies on a formula diet are more exposed to infections.  Economists' forecasts have also pointed to avoidable health and environmental costs arising from reduced breastfeeding, and these are found to be considerable. Conclusion: The use of BMS has a detrimental effect on both mankind and nature, while breastfeeding is still the most eco-friendly and health-producing feeding technique.  Novelty/Originality: Besides being the first study to establish BMS consumption with environmental contamination, carbon footprints, and health outcomes in Southeast Asia, this review also redefined infant feeding as an issue of planetary health.